Aligning green infrastructure to sustainable development: A geographical contribution to an ongoing debate. Issue 2 (29th November 2021) - De Vito, Laura; Staddon, Chad; Zuniga‐Teran, Adriana A.; Gerlak, Andrea K.; Schoeman, Yolandi; Hart, Aimee; Booth, Giles
Abstract: Blue and green infrastructure (BGI) is increasingly viewed as a promising solution to promoting a shift beyond traditionally engineered "grey" approaches towards more socially and environmentally sustainable infrastructure systems. The specific insights of geographical scholarship on how to address issues of processes, scale, and place in BGI design, implementation, and long‐term management would help unlock the potential for BGI to be appropriate and inclusive, as well as support environmentally sound solutions. In this paper we unpack issues of processes for inclusive decision‐making to design and implement BGI projects that can advance sustainable development. We present an assessment framework and its application to two case studies that highlight the potential for better alignment of BGI projects to the three pillars of sustainable development and that reveal key research challenges that geographical scholarship could address. We believe that co‐produced geographical research in this domain is well placed to tackle these research challenges. Abstract : The paper presents a framework to better align blue and green infrastructure to sustainable development through appropriateness and inclusivity. It highlights the contribution of geographical scholarship to this ongoing debate.